Secular variation and reversals in a composite 2.5 km thick lava section in central Western Iceland (Dataset) ... - Kristjánsson, Leó; Jóhannesson, Haukur (Magnetics Information Consortium (MagIC), 2023)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Secular variation and reversals in a composite 2.5 km thick lava section in central Western Iceland ...